Justified Limits on Refusing Intervention - Chervenak, Frank A. (The Hastings Center report, 1991)
Physicians may justifiably limit patients' refusals of medical interventions when the refusal is based on a negative right to noninterference coupled with a request for an unreasonable alternative.